Narrow Row Cotton Evaluation, Marana Agricultural Center - Thacker, Gary W. (College of Agriculture, University of Arizona (Tucson, AZ), 1987)
In a preliminary, unreplicated test, cotton was planted in 40 inch and 27 inch rows on April 10 and again on May 1. Narrow rows outyielded 40 inch rows at both planting dates. The yield difference between the row spacing treatments was greatest in the May 1 planting. Both row spacings had higher yields when planted on the later date, as did both the DPL 90 and ST506 varieties used in the test.